Changing the paradigm of cervical cancer prevention through introduction of HPV-testing: evaluation of the implementation process of the Jujuy Demonstration Project in Argentina - Arrossi, Silvina (2021)
Introduction: The Jujuy Demonstration Project (JDP) was a project carried out over the course of 4 years (2011-2014) to develop, implement and evaluate the programmatic components of a Human Papilloma Virus (HPV)-based screening programme in Argentina. The aim of this paper is to present a qualitative evaluation of the context and implementation process of the JDP. Methods: We used an adaptation of the Health System Framework (HSF), which includes interconnected contextual factors that are considered key drivers for successful health interventions. We reviewed secondary documents, which included scientific reports, norms and regulations, information sheets, power point presentations and manuals and recommendations published by the National Programme for Cervical Cancer Prevention. We also carried out semi-structured interviews with key informants to explore their views about technology acceptability. Results: Key components of the JDP implementation process were: a high level of political support and consensus among stakeholders, the demonstrated effectiveness of the technology and its acceptability by health authorities and providers, the funding of tests and diagnosis/treatment services, the implementation of an information system for monitoring and evaluation and the reorganisation of the network of screening, diagnosis and treatment services. Conclusion: This analysis examines the policy context in which the JDP was implemented and the system components that were key for the demonstrated effectiveness of the strategy. Such analyses provide useful insights into core components of HPV testing implementation that are needed to guarantee its potential effectiveness to reduce cervical cancer incidence and mortality.